Family visitation in greek intensive care units: Nurses' perspective - Athanasiou, Archonto; Papathanassoglou, Elizabeth; Patiraki, Elisabeth; McCarthy, Mary S.; Giannakopoulou, Margarita (My University, 2014)
Background Policies of flexible and open visiting in intensive care units benefit both patients and patients' families. In Greek intensive care units, gaps exist between evidence and practice for family visitation, resulting in restricted visiting policies. Objectives To explore the beliefs of nurses in Greek intensive care units about the effects of visiting on patients, patients' families, and unit staff and nurses' attitudes toward visiting policies. Methods A descriptive correlational survey was conducted in 6 public hospitals in Athens, Greece, with a sample of 143 critical care nurses. Data were collected via an anonymous questionnaire consisting of 3 validated scales to assess the nurses' beliefs about and attitudes toward visitation. Results Generally, nurses were resistant to family visiting and open visiting, and most (94.4%) did not want an open policy in their unit. Nurses think that open visiting policies are supportive for patients and patients families, but the overall effects of visiting depend on both the nurse and the patient (91.6%). Nurses reported that open visiting created increased physical and psychological burdens for them (87.5%) and hampered nursing care (75.5%). Years of work experience, staffing level, and number of night shifts worked by nurses per 15 days were factors predictive of nurses' attitudes toward and beliefs about family visitation. Conclusions Nurses' beliefs about and attitudes toward visitation are important factors in the implementation of more flexible visiting policies in Greek intensive care units. Well-staffed units with experienced nurses and fewer shifts per week may affect nurses' negative attitude toward open visitation. (American Journal of Critical Care. 2014;23:326-333).
Keywords: Female; Family; Greece; Health personnel attitude; Human; Intensive care nursing